Proceedings of the 19th ACM Symposium on Virtual Reality Software and Technology 2013
DOI: 10.1145/2503713.2503751
|View full text |Cite
|
Sign up to set email alerts
|

Impact of graphical fidelity on physiological responses in virtual environments

Abstract: Higher quality computer graphics in interactive applications in the areas of virtual reality and games is generally assumed to create a more immersive experience for the end user. In this study we examined this assumption by testing to what degree graphical fidelity was associated with physiological arousal as measured by a galvanic skin response (GSR) sensor. Thirty-six subjects played two different video games at the highest and lowest graphical quality settings while their GSR activity was measured. No sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…More specifically, physiological signals of skin conductance and heart rate have been suggested to assess emotional states as objectives measures for people's responses in virtual environments [15]. Using a GSR sensor to measure physiological arousal, it was found that graphical fidelity is not correlated with GSR response [27]. To consider the effect of changes in scene brightness on the pupillary response for 2D screens and VR HMDs (head-mounted displays), an individual calibration procedure and constriction-based models of pupil diameter have been proposed [16].…”
Section: User Perceptions and Physiological Responsesmentioning
confidence: 99%
See 3 more Smart Citations
“…More specifically, physiological signals of skin conductance and heart rate have been suggested to assess emotional states as objectives measures for people's responses in virtual environments [15]. Using a GSR sensor to measure physiological arousal, it was found that graphical fidelity is not correlated with GSR response [27]. To consider the effect of changes in scene brightness on the pupillary response for 2D screens and VR HMDs (head-mounted displays), an individual calibration procedure and constriction-based models of pupil diameter have been proposed [16].…”
Section: User Perceptions and Physiological Responsesmentioning
confidence: 99%
“…We suggest future research on additional features (e.g. fixations and saccades) and user-perceived sensory fidelity in different simulation environments for enhancing the user experience of presence [27,29] to make different driving situations more distinctive.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
See 2 more Smart Citations